Increased apoptosis, but not pancreatic duodenal homeobox-1 expression in pancreatic islets is associated with intermittent glucose loads in mice - Lilik Herawati; Kristanti Wanito Wigati; Purwo Sri Rejeki; Widjiati Widjiati; Roedi Irawan (Сахарный диабет)
Background: Several caloric restriction studies revealed good for diabetes prevention. However, prevalence of it seems rising yearly. It needs alternative technique thus people can choose suitable way for them. Aim: To determine the effect of glucose diet intermittently on pancreatic duodenal homeobox-1 (PDX-1), apoptosis in pancreatic islets, and pancreatic islets area. Materials and methods: Balb/c mice were divided into five groups. Control group was given standard diet. The Continuous group was given standard diet and added with 7.4% calories continuously. The 1x, 2x, and 3x intermittent groups were given standard diet and added 7.4% calories for 1x, 2x, and 3x/week respectively. The 7.4% calorie addition was a glucose solution by oral galvage and ad libitum for 8 weeks. Results: There was a significantly difference on apoptosis density (p=0.043), but not in PDX-1. The islets Int2x and Int3x groups showed a significant decrease than control group (p=0.048). Insulin serum levels increased significantly in Continuous group compared to control group (p=0.04). In addition, the insulin serum level of 1x and 3x intermittent groups were significantly lower than Continuous group (p<0.05). Pre-post blood glucose levels on treatment groups decreased significantly compared to control group (p=0.012). Conclusions: Continuous and 1-3x/week intermittent addition of 7.4% calories of glucose for 8 weeks indicate a compensation mechanism for maintaining homeostasis, such as increase insulin serum level and seem to initiate the changes of morphologic-biomolecular (mainly apoptosis density in islets). The better mode is 1x/week of additional calories. However it needs further exploration to find out other influenced factors for these mechanism discovery.